Standardizing the Project Management process for New Product Development - Hansson, Carolina; SMITH, SÉBASTIEN (My University, 2018)
This thesis work was generated upon the lack of delivery efficiency and delivery deviations between projects conducted to develop new products by the hydraulic attachment tools division (HAT) of Epiroc, company acting in the mining and construction industry on a global scale. The aim of this work was therefore to analyze the current new product development process for the HAT product company in Kalmar (SE) and the one in Essen (DE) and identify and propose improvement to this process by standardizing the project management process for new product development on a divisional level. The objective therefore concerns the identification of main issues with the current new product development processes at Epiroc which generates most delays and inefficiencies in projects. In addition, the main obstacles to standardization of the process between both product companies were questioned, and finally the needed aspects enabling a standardization of the new product development process on a divisional level were established. The hereby study represents a qualitative research using a abductive research approach and systematic combining. The qualitative data used to generate results was acquired through 21 semi-structured interviews with key members of both product companies and through 12 feedback sessions with similar key members. Triangulation of data was also used to support the authenticity of the study as well as a quantitative statistical analysis of key problem areas. As a result, this study permitted the obtaining of a fully standardized first phase of a 5 phases stage gate process for new product development. The following 4 phases are developed but not fully standardized due to the discovery of deviations and disagreements in the organizational structure and stage gate approach. The cost allocation process, usage of the ERP system and difference in project manager roles between the two product companies represent the deviation hindering the possibility of a complete standard process for the HAT division. Disagreements such as location of phase transition, respect of theory and overlapping of phases versus frontloading were drawn from the deviations and thoroughly described as obstacles to the standardization of the divisional process. Finally, this study proposes further research to be done and suggestion of key activities to complete in order to reach a fully standardized new product development process for the HAT division of Epiroc.
Keywords: Samhällsbyggnadsteknik; Civil Engineering